2015
DOI: 10.1002/htj.21198
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance Improvement of Tractor Radiator Using CuO/Water Nanofluid

Abstract: This research work discusses the heat transfer improvement in a tractor radiator with nanosized particles of CuO with water as base fluid. The nano materials and its suspension in fluids as particles have been the subject of intensive study worldwide recently since pioneering researchers recently discovered the anomalous thermal behavior of these fluids. The engine cooling in heavy vehicles is an important factor for their performance in the intended application. Here, the tractor engine radiator cooling is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…This could be the reason behind the limited fouling studies in such heat exchangers. In the past few decades, the nanotechnology was used extensively to improve the heat exchanger performance by adding different types and concentrations of nanoparticles to the working fluids . It has been reported that the presence of nanoparticles in the working fluid affects the heat transfer rate by different mechanisms such as: thermophoresis and Brownian motion with closure formation .…”
Section: Introductionmentioning
confidence: 99%
“…This could be the reason behind the limited fouling studies in such heat exchangers. In the past few decades, the nanotechnology was used extensively to improve the heat exchanger performance by adding different types and concentrations of nanoparticles to the working fluids . It has been reported that the presence of nanoparticles in the working fluid affects the heat transfer rate by different mechanisms such as: thermophoresis and Brownian motion with closure formation .…”
Section: Introductionmentioning
confidence: 99%
“…The effective density, which is a parameter of concentration of the nanofluid, is given by ρnf=1φρbf+φρp.…”
Section: Physical Properties/mathematical Modelmentioning
confidence: 99%
“…The specific heat of the nanofluid is a function of concentration of the nanofluid and specific heat of the base fluid (Cpρ)nf=()()1φCpbf+φCpρp…”
Section: Physical Properties/mathematical Modelmentioning
confidence: 99%
“…Nanofluids have demonstrated better thermal characteristics; thus they are suitable for electronic cooling systems, car/tractor radiator, heat exchanger liquids, solar systems, and nuclear reactors. Several cases related to the heat transfer of nanofluids have been presented …”
Section: Introductionmentioning
confidence: 99%
“…Several cases related to the heat transfer of nanofluids have been presented. [18][19][20][21][22][23][24][25][26][27][28] According to the previous studies about the natural convection flow inside enclosures, investigating the effect of deviation angle of enclosure on flow field, heat transfer, and entropy generation of turbulent natural convection in a tall enclosure has not been noticed recently. Consequently, this study investigates this issue by using the computational fluid dynamicsartificial neural network (CFD-ANN) hybrid method.…”
mentioning
confidence: 99%